The Development of Environmentally Friendly Concrete in Sustainable Construction in Indonesia: A Literature Review - Nurul Aisyah Azis; M Awaluddin A; Faradhiya Jinan Bastini; Musdalifah (Jurnal Teknik Sipil, 2026)
The construction industry is one of the significant contributors to carbon emissions, primarily through cement production as the main constituent of concrete. Efforts to reduce the carbon footprint have driven the development of environmentally friendly concrete through the utilization of supplementary cementitious materials and alternative non-cement binders. This study aims to develop a literature synthesis on the advancement of environmentally friendly concrete in Indonesia, to analyze its mechanical performance and durability characteristics, and to evaluate its implications for sustainable construction. The research employs a narrative literature review method, covering national and international publications from 2005 to 2025 relevant to supplementary materials, geopolymer concrete, and sustainability assessment. The findings indicate that the use of fly ash, slag, and silica fume as partial cement replacements can achieve competitive mechanical performance while enhancing resistance to aggressive environmental conditions. Geopolymer concrete also demonstrates significant potential for carbon emission reduction while maintaining adequate structural performance. However, widespread implementation remains constrained by challenges such as variability in material quality, limited technical standards, and industry readiness. This study provides an integrated synthesis of technical and environmental aspects as a foundation for strengthening the adoption of low-carbon concrete in supporting sustainable construction in Indonesia.